Brain derived neurotrophic factor in multiple sclerosis: effect of 24 weeks endurance and resistance training. (16th March 2016) - Wens, I.; Keytsman, C.; Deckx, N.; Cools, N.; Dalgas, U.; Eijnde, B. O.
Abstract : Background and purpose: Brain derived neurotrophic factor (BDNF) is suggested to play a neuroprotective role in multiple sclerosis (MS). However, the BDNF response to long‐term exercise in MS remains unknown. Our objective was to compare resting BDNF profiles of healthy controls (HCs) and persons with relapsing−remitting MS (RRMS) and to investigate the impact of a 24‐week exercise intervention on serum BDNF release in MS. Methods: At baseline, blood BDNF levels were assessed in MS ( n = 22, mean Expanded Disability Status Scale 2.6 ± 0.2, mean age 43 ± 2 years) and HCs ( n = 19, mean age 47 ± 1 year). Next, persons with MS were randomized to an exercise intervention group (EX, n = 15) or a sedentary control group (SED, n = 7) completing a 24‐week randomized controlled trial. In persons with MS, muscle strength, exercise tolerance and body composition were assessed, as compliance measures, at baseline and after 24 weeks. Results: At baseline, the BDNF concentration of persons with RRMS was 21% lower than HCs. Following 24 weeks of intervention, changes in BDNF concentrations differed significantly between EX and SED. In particular, within EX BDNF concentrations increased 13.9% ± 8.8%, whereas it decreased 10.5% ± 4.1% within SED. Furthermore, 24 weeks of exercise induced changes in the compliance measures between EX and SED. In addition, within EX muscle strength, exercise tolerance and lean tissue mass improved, whereas these remained stable within SED. Conclusion: In conclusion, BDNF concentration of persons with RRMS was lower compared to HCs and increased after 24 weeks of exercise in persons with MS, compared to the non‐exercise MS control group.